Związki przymiotnika "były" z rzeczownikami - Adrianna Piotrowska (Ksiegarnia Akademicka Publishing, 2019)
Connectivity of the Adjective były ‘Former’ with Nouns The paper discusses the grammatical and semantic characteristics of the adjective były ‘former’, with a particular regard to its connectivity with nouns. The adjective były is an element of a nominal group, it connotes a noun on the right side, and cannot be used in the function of a predicate. It connects with certain groups of common nouns which denote people and artifacts, as well as with geographical names; it does not connect with names of animals or plants.